PENGARUH EFEKTIFITAS PEMBERIAN TERAPI AKTIVITAS KELOMPOK DAN TERAPI PSIKORELIGIUS TERHADAP KEMAMPUAN KLIEN MENGONTROL HALUSINASI DI RUANGAN NYIUR RSKD PROVINSI SULAWESI SELATAN - Abdul Thalib Hamzah (Stikes Graha Edukasi Makassar, 2018)
Objective: The purpose of this study is to influence the effectiveness of group therapy therapy and psychoreligious therapy on the client's ability to control hallucinations in the RSKD room of South Sulawesi Province. Methods The research design used in this study is the method of Pre Experiment: One group pretest-posttest design that this research has the characteristic of expressing the causal relationship by involving the treatment group. the treatment group in the observation before the intervention, then in the observation again after intervention. The sample size in this study were 58 respondents in accordance with inclusion criteria. Data collection is done by using observation sheet. Results: The results showed that there was Effectiveness of group therapy therapy and psychoreligious therapy on client's ability to control hallucinations in RSKD South Sulawesi Province (p = 0,000). Discussion: Hallucinations are one of the symptoms of mental disorders in individuals characterized by perceptual sensory changes in the form of sound, sight, smell, touch, and client covering feel the actual stimulus does not exist. Conclusion: The conclusion of this research is Effect of giving group therapy therapy and psychoreligius therapy to client's ability to control hallucinations in RSKD room of South Sulawesi Province. Suggestion This research is expected to provide valuable knowledge and skills for researchers so that it can apply nursing care, especially the application of group therapy therapy and psychoreligious therapy to mental disorders patients